2019
DOI: 10.22605/rrh4978
|View full text |Cite
|
Sign up to set email alerts
|

What about the health workforce distribution in rural China? An assessment based on eight-year data

Abstract: Introduction: Health, as a fundamental human right, and its fairness and equality have gradually been reiterated and emphasized around the world. The inequality in health workforce distribution is common in China and many other developing countries. However, it is unknown whether the economic conditions and insufficient supply of village physicians in rural areas worsens health inequality. This study and article aimed to explore and discuss the inequality in health workforce in rural China. Methods: Inequality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Health is a fundamental human right, and the issue of health equality has attracted significant attention and extensive discussion worldwide (1,2). Excessive health inequality will disrupt social harmony, cause a series of problems such as income inequality, and pose immense threat to labor quality and sustainable economic development as well (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health is a fundamental human right, and the issue of health equality has attracted significant attention and extensive discussion worldwide (1,2). Excessive health inequality will disrupt social harmony, cause a series of problems such as income inequality, and pose immense threat to labor quality and sustainable economic development as well (3).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we still use the name of New Rural Social Pension (NRSP) in the following discussions 2. Agricultural labor is defined as work in agriculture, forestry, animal husbandry, sideline, and fishery, and non-agricultural labor is defined as work in other industries.…”
mentioning
confidence: 99%
“…The Theil L index has the advantage of decomposition, which means decomposing the total national inequality to inner-regional difference and inter-regional difference (Anand, 2010;Zhou et al, 2015;Ren et al, 2018). More details about the methods could be seen in the authors' another research (Yang, Wang, and Xue, 2019).…”
Section: Measures Of Inequalitymentioning
confidence: 99%
“…The inequalities in high-quality health service supply, especially in PHC, remained a serious challenge to China's healthcare system, as well as the whole world (Gao et al, 2002;Wang, Wang, and Maitland, 2012;Chen et al, 2019). In China, the gap between supply and demand, urban and rural areas, the Eastern area and the Western area, and the health institutions in the grass-roots level and tertiary hospitals in health service has always been the great obstacles to promoting and protecting the health of the whole nation (Wang, Wang, and Maitland, 2012;Wu et al, 2017;Yang, Wang, and Xue, 2019). The utilization of PHC in China is low (Zou et al, 2015), and patients prefer to tertiary comprehensive hospitals for high-quality health service and medical technology (Jiang et al, 2015), which causes the misuse of the medical resources, higher medical costs under the medical reimbursement policy, and the overload in the tertiary comprehensive hospitals leading to more medical conflicts and lower satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, for a long time, the shortage of personnel is prominent due to di culties in recruitment and serious wastage in rural health institutions, especially township health centers (3). A study conducted by Yang et al (4) indicated that China's rural health resources are extremely de cient, compared with other types of human resources for health. The shortage of professionals in health care centers will eventually affect the health of the rural population and exacerbate health inequality.…”
Section: Introductionmentioning
confidence: 99%